Viajando por terras portuguesas: um estudo de Janelas verdes, de Murilo Mendes, e Viagem a Portugal, de José Saramago - Ozana Aparecida do Sacramento (2011)
This study proposes a critical reading of travel writing Janelas Verdes, by Murilo Mendes, and Viagem a Portugal, by José Saramago. It demands to understand the implications of the concept of travel writing of both writers, and that notion was creatively appropriate for them in their predecessors reports. We tried to observe the conditions and specifications of travel writing, and how the literary works chosen for this work is toward or away from the paradigms of the genre "travel writing". It aim at the intersection of look and read, reflect and feel, we characterize the view that each of the two writers - Saramago and Mendes throws on Portugal his landscapes, as well as on the travelers conditions, whose body and / or perspective displacements will triggering modulations and blends in the space. In this sense, we intend to understand how travel is established as a cognitive operator that allows a transit through geographic space, the literary space, reflection and the passage of one another to anchor itself in unsuspected perspectives, geographies and otherness.